Writing Early Modern Loneliness
XIII, 300 p. 7 illus., 5 illus. in color.
Keywords: Through a wide-ranging and methodologically astute investigation of early modern expressions of loneliness and solitude, this volume makes a valuable contribution to the History of Emotions by providing a useful corrective to the view of the early modern world as communal and where the existence of God and the consequent comfort that knowledge provides are taken as given. —Cathy Shrank, University of Sheffield, UK This interdisciplinary collection of ten essays is the first to redefine historical conceptions of “loneliness” in the Western world by exploring its manifestation in early modern textual sources. Contrary to current scholarly consensus that loneliness in Britain was understood as an emotion from the late eighteenth century, only beginning to emerge in its literary form in the writings of the Romantic poets, the contributors in this volume argue that early modern people were capable of complex and conflicting feelings of social and emotional isolation which were expressed in a wide range of writings. Moreover, these products of loneliness continue to resonate poignantly with humanity today. Hannah Yip is a Leverhulme Early Career Fellow at the University of Manchester, UK. Her current research interests centre on the cultural and emotional lives of clergymen in the English Reformation. She has held Fellowships at the Huntington Library, the William Andrews Clark Memorial Library, and the John Rylands Library. Thomas Clifton PhD MA PGCE (PCET) is a Lecturer in Academic Writing at the Centre for Academic Writing, Coventry University, UK. Thomas completed an AHRC-funded PhD on “Textual Practices in Meditative Writing, 1661–1678” at the University of Birmingham and an MA in early modern literature at Bangor University. Thomas’s research interests include dialogical thought processes in meditative, reflective, and self-writing, historically and contemporarily, and the fluidity of genre in the early modern period. .